Development of a Complaint Application for the Education Agency Using the Agile Development Method - Sinta Tumbo; Medi Hermanto Tinambunan (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
The rapid advancement of information technology has driven changes in performance and problem solving in society and government agencies. In the education sector, the Education Office, as the main service provider, requires an effective complaint mechanism for students, teachers, employees, and the community. The current complaint method still often relies on face-to-face submission, which causes problems such as difficulty in tracking the status of complaints, poor documentation, and limitations in evaluating the quality of complaint handling. This study aims to develop a web-based complaint application to digitize and harmonize the complaint process at the Minahasa Regency Education Office. The Agile Development method was used due to its iterative, flexible, and collaborative nature, allowing for the gradual development of features based on direct feedback from stakeholders. Data collection techniques included observation, interviews, documentation studies, and literature studies. The system was designed using UML diagrams, including Use Case, Activity, Sequence, and Class diagrams. Development was carried out in sprints, focusing on core features: user registration with NIK verification, complaint submission and tracking, and an admin dashboard for complaint management. Functional testing using the Black-Box method confirmed that all key features operate correctly as required. The resulting application successfully transformed the manual complaint process into a more structured, transparent, and efficient digital system, thereby contributing to improved public service quality in the field of education.